Calculation of loading-induced tendon slip in beams prestressed with external tendons. Part II: Numerical analysis - Diep, Bui Khac; Quang, Lam Huu (Vietnam Journal of Mechanics, 2006)
In this paper, a computing method for the tendon slip based on the force equilibrium condition at deviators was proposed. The proposed method for the evaluation of tendon slip was presented in a general form by taking into account all possibilities of tendon slip at deviators, and several factors found to be important that affect the tendon slip, such as effects of the slippage at two adjacent deviators, friction, change of tendon angles during the applied load, etc. The validation of the proposed method was verified by comparing with the experimental results. The predicted results showed a close agreement with the experimental observation.